Women of Color Health Activists, Self-Help, Community, and Care - Elizabeth Hearne (Journal of Women's History, 2026)
Abstract: In the 1980s and 1990s, some women of color health activists in the United States theorized their own methods for emotional care and healing. This article details the development, practice, challenge, and legacy of psychological Self-Help in the National Black Women's Health Project and beyond. It also frames Self-Help in a background historical context. Activists' oral histories and archival documents reveal how they approached the care of individual and collective traumas, including racial trauma. Their methods show the healing potential of intersectionality as an ethic and an approach. These approaches reframed and democratized the scope, purpose, and methods of giving and receiving emotional and psychological care.